Improving the ability of writing advertising sentences in students - Amri As; Ratu Wardarita; Dessy Wardiah (JPGI (Jurnal Penelitian Guru Indonesia), 2021)
The purpose of this study was to improve the students' ability to write classified ad sentences in class IXA SMP Negeri 14 OKU . Research data collection techniques using observation, tests, documentation. The research data analysis technique used observation to see the activeness of student learning and the test of understanding writing classified advertisements . Based on the analysis of research data on the improvement of writing classified ad sentences in cycles I and II, the following results were obtained. The results of the first cycle test showed that the average increase in writing classified ad sentences for students was 61.45. Average it rose to 94.45 or 53.7% in cycle II. The increase in the classical average was also followed by the increase in the scores obtained by the students in each aspect of the assessment of writing classified ad sentences . The improvement in writing student classifieds sentences in each cycle was followed by changes in the students ' behavior in a positive direction . This can be seen in the activeness and enthusiasm of students in receiving learning because students feel happy and interested in participating in learning to write classified ad sentences through . From these results, suggestions can be taken by the researcher, the researcher me recommend , among others, 1) teachers should use teaching methods that vary to attract students, and 2) The researchers or teacher education field of language Indonesia should be able to conduct similar studies yet with different methods in order to obtain various learning methods through.